Contact and Plasmin Kinin-Forming Systems in the Blood - Buluk, K; Czokało, Maria; Małofiejew, M (Thrombosis and Haemostasis, 1970)
By means of preparations of two different kininogens, the existence of two kallikreins, postulated previously, that is one activated by the contact factor – contact kallikrein, and another by plasmin – plasmin kallikrein, has been confirmed.Stasis plasma or plasma from blood taken without stasis incubated at 37 ° C can be a source of contact kallikrein.It was found that modified plasma, that is plasma acidified to pH 2 and realkalized after 10 min, is suitable material for demonstrating that plasmin activates plasmin kallikrein. Plasmin kallikrein in the plasma has two substrates: kininogen – from which it releases kinins, and contact kallikrein which it inactivates. A diagram showing the activation of kinin-forming systems in the blood plasma is proposed.